Efektivitas Penyediaan Air Bagi Satwa Liar di Taman Nasional Way Kambas Saat Musim Kemarau - Master, Jani; Pransisca, Alda; Suratman (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
Way Kambas National Park (TNWK) in Lampung Province is experiencing prolonged drought, prompting the need for artificial water sources for wildlife. This study evaluated natural water conditions and compared three water provision methods. Conducted in collaboration with the Sumatran Tiger Conservation Foundation (October–December 2023), the research covered SPTN I Way Kanan (Rawa Bunder and Way Kanan Resorts) and SPTN III Kuala Penet (Margahayu Resort) in TNWK. Parameters included salinity measurements of natural water and testing plastic tubs, tarpaulin ponds, and their combination at 12 sites, monitored using trap cameras.The results showed that the Way Kanan River, the only remaining natural water source, had high salinity (13–15‰). Wildlife activity was higher at plastic tubs than at tarpaulin ponds, based on trap camera data. Key words: wildlife water developments, drought, Way Kambas National Park.